Upaya Konseling Dalam Menangani Korban Kekerasan Pada Anak Di Pusat Pelayanan Terpadu (PPT) “Jayandu Widuri” Kabupaten Pemalang - Zakia Latifah; Arri Handayani; Venty Venty (PT. ALHAFI BERKAH INDONESIA, 2023)
Violence against children is rampant everywhere and is a problem that is difficult to address, but efforts are still being made by related parties, such as the role of the government, legal institutions and others. The aim of this research is to determine the supporting and inhibiting factors for counseling for victims of child violence as an effort to treat victims of violence against children at the Integrated Service Center (PPT)